(untitled) (Journal of the Management Sciences, 2023)
There is dearth of empirical studies on the relationship between strategic decision-making and product quality, particularly as it concerns pharmaceutical firms in Nigeria. In order to fill this lacuna in the management literature, this study was carried out to assess the effect of strategic decision-making on product quality of selected pharmaceutical firms in Nigeria using cross-sectional design. The study population comprised a total of eight hundred and ninety (890) employees of three (3) pharmaceutical firms. The sample size of two hundred and seventy-six (276) respondents was drawn from the population of the study using proportionate sample size determination formula. Data were generated using structured questionnaire and analyzed using both descriptive (mean) and inferential statistics (multiple regression analysis). The results indicated that the strategic decision-making of the studied pharmaceutical firms. It was found that decision quality, decision routine and decision commitment had insignificant influence on product quality. The implication of the result is that the overall quality of decisions as well as consistency of decision taken by pharmaceutical firms relative to their set objectives has not been efficient. In view of the findings, the study recommended that there should be a periodic review of the strategic decision-making process of the pharmaceutical industry to ensure that it is in line with the dynamic business environment, engagement of risk managers and experienced production line managers towards improving the quality of decisions and ensuring product quality.